Eczema in pregnancy. Issue 7611 (19th July 2007) - Weatherhead, Sophie; Robson, Stephen C; Reynolds, Nick J
Abstract : Many women with eczema experience flares during pregnancy, and management must take account of the possible effects of some treatments on the fetus